miR-100-5p Downregulates mTOR to Suppress the Proliferation, Migration, and Invasion of Prostate Cancer Cells - Ye, Yun; Li, Su-Liang; Wang, Jian-Jun (Frontiers in Oncology, 2020)
Background: Previous studies have shown that miR-100-5p expression is abnormal in prostate cancer. However, the role and regulatory mechanism of miR-100-5p requires further investigation. Thus, the aim of this study was to observe the effects of miR-100-5p on the proliferation, migration and invasion of prostate cancer (PCa) cells and to explore the potential related regulatory mechanism. Methods: Differential miRNA expression analysis was performed using next-generation sequencing (NGS) in the PCa cell line LNCaP and the normal prostatic epithelial cell line RWPE-1. The expression levels of miR-100-5pwere detected using real-time fluorescence quantitative PCR (qRT-PCR). LNCaP cells were transfected with NC-mimics or miR-100-5p mimics by using liposome transfection. Moreover, the CCK-8 proliferation assay, cell scratch assay and Transwell assay were used to detect the effects of miR-100-5p on cell proliferation, migration and invasion. In addition, the potential target gene of miR-100-5p was predicted, and the influence of miR-100-5p on the expression of mTOR mRNA by qRT-PCR and the expression of mTOR protein was detected by western blot and immunohistochemical staining. Results: Differential expression analysis of high-throughput sequencing data showed low expression of miR-100-5p in the PCa cell line LNCaP. It was further confirmed by qRT-PCR that the expression of miR-100-5p in LNCaP cells was significantly lower than that in RWPE-1 cells (P<0.01). miR-100-5p expression in LNCaP cells was markedly upregulated after transfection with miR-100-5p mimics (P<0.01), while cell proliferation, migration and invasion capacities were clearly reduced (P<0.01), and mTOR mRNA and protein expression was also substantially lowered (P<0.01). Finally, we further confirmed by immunohistochemical staining that miR-100-5p regulated the expression of mTOR. Conclusion: miR-100-5p is expressed at low levels in LNCaP cells, and it can suppress LNCaP cell proliferation, migration and invasion, the mechanism of which is related to downregulating the expression of mTOR.